Does it matter when your smartest peers leave your class? Evidence from Hungary - Schiltz, F; Mazrekaj, D; Horn, D; De Witte, K (Elsevier, 2019)
Elite schools in Hungary cherry pick high achieving students from general primary schools. The geographical coverage of elite schools has remained unchanged since 1999, when the establishment of new elite schools stopped. We exploit this geographical variation and estimate the impact of high achieving peers leaving the class on student achievement, behaviour, and aspirations for higher education. Our estimates indicate moderate but heterogeneous effects on those left behind in general primary schools.